Social attractiveness of Russian higher medical education for international students - V. I. Chumakov; R. R. Farmanyan (Кардиоваскулярная терапия и профилактика, 2023)
The article is devoted to the study of social attractiveness of Russian higher medical education for foreign students. The importance of promotion of educational services of Russian universities is highlighted. Criteria for choosing a university by foreign students were assessed. The importance of modern and effective communication channels of the university and foreign applicants, modern infrastructure and learning technologies was determined. The work contains recommendations for improving the attractiveness of medical universities for foreigners.